The Employee Performance Analysis in Changes Work Method to Remote Work Patterns in The New Normal Era - Antonius Sony Eko Nugroho (Entrepreneurship Faculty, Universitas Garut, 2021)
Abstract – In 2020 the Covid-19 pandemic has impacted all working area aspect, which requires every organization to make changes quickly and adaptively. Companies are accelerating the use of digital technology, including changing the way they work. This research is focused on analyzing employee performance when there is a change in the way of working from the office to a remote way of working from different locations in the new normal era. This qualitative research uses a phenomenological method approach that utilizes interviews as a means to collect the necessary data and is combined with a netnographic method approach to explore data on the internet. This employee performance analysis is carried out in IT-based organizations, where employees as audiences and managers are considered as parties who can provide performance appraisals with changes in work methods to remote work patterns in the new normal era, as well as its relation to the readiness of technology and its impact on employee performance. The evaluation results show that employee performance is also influenced by the readiness of supporting technology, where in the new normal era with remote work patterns, of course, have challenges in implementing comfortable and safe remote access, so that all activities may run well and smoothly.